Carbonic Anhydrase Inhibitors suppress platelet procoagulant responses and in vivo thrombosis: Carbonic Anhydrase Inhibitors as Antithrombotics. (2nd October 2020) - Agbani, Ejaife O.; Zhao, Xiaojuan; Williams, Christopher M.; Aungraheeta, Riyaad; Hers, Ingeborg; Swenson, Erik R.; Poole, Alastair W.
Abstract: Carbonic anhydrase (CA) inhibitors have a long history of safe clinical use as mild diuretics, in the treatment of glaucoma and for altitude sickness prevention. In this study, we aimed to determine if CA inhibition may be an alternative approach to control thrombosis. We utilized a high-resolution dynamic imaging approach to provide mechanistic evidence that CA inhibitors may be potent anti-procoagulant agents in vitro and effective anti-thrombotics in vivo . Acetazolamide and methazolamide, while sparing platelet secretion, attenuated intracellular chloride ion entry and suppressed the procoagulant response of activated platelets in vitro and thrombosis in vivo . The chemically similar N-methyl acetazolamide, which lacks CA inhibitory activity, did not affect platelet procoagulant response in vitro . Outputs from rotational thromboelastometry did not reflect changes in procoagulant activity and reveal the need for a suitable clinical test for procoagulant activity. Drugs specifically targeting procoagulant remodeling of activated platelets, by blockade of carbonic anhydrases, may provide a new way to control platelet-driven thrombosis without blocking essential platelet secretion responses. Graphical Abstract: